Case Report: Anti-Cholinergic Syndrome Induced by Papaver Rhoeas Plant and Its Management - Salih Denis Şimşek; Ökkeş Zortuk; Faris Arda Dönmez; Sergen Bağdad; Mustafa Polat (Global Emergency and Critical Care)
Anti-cholinergic toxic states are a group of pathological conditions commonly observed in emergency departments (EDs) and are rarely fatal. The plant Papaver rhoeas (commonly known as red corn poppy or common poppy) is used in traditional medicine and as a food source in regions of Türkiye and Iran. The toxic effects of this agent can result from incorrect or excessive use. A 61-year-old female patient with a history of chronic obstructive pulmonary disease presented to the ED after consuming a dish made with Papaver rhoeas. On arrival, the patient presented with hypertension symptoms, altered consciousness, and muscle fasciculations. On monitoring, she was found to be tachycardic with a heart rate of 130 beats per minute and hyperthermic with a temperature of 37.8 °C. Blood pressure measurements showed a systolic pressure of 180 mmHg and a diastolic pressure of 110 mmHg. Supportive therapy was administered and diazepam was used following the development of seizures. The patient was given physostigmine, and after intensive observation, her symptoms improved and she was safely discharged. Anticholinergic toxidrome are common in ED presentations. Allergic reactions, convulsions, and hepatotoxicity may also occur after exposure to Papaver rhoeas. Although these conditions are generally not fatal, appropriate ED management can prevent morbidity and mortality.